Report on Media Training Workshop on Climate Smart Livestock Feed and Forage Innovations - Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra; Seifu, Haimanot; Mesfin, Hailemariam (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The International Livestock Research Institute (ILRI) works for better lives through livestock in developing countries. ILRI is co-hosted by Kenya and Ethiopia, has 14 offices across Asia and Africa. ILRI is one of the CGIAR research centres, a global research partnership for a food-secure future. CGIAR science is dedicated to reducing poverty, enhancing food and nutrition security, and improving natural resources and ecosystem services. Its research is carried out by 15 CGIAR centres in close collaboration with hundreds of partners, including national and regional research institutes, civil society organizations, academia, development organizations and the private sector. Africa RISING is a USAID funded program that operates in six African counties (Mali, Ghana, Tanzania, Malawi, Zambia and Ethiopia). The program aims to contribute to Feed the Future goals of reducing hunger, poverty and under-nutrition by delivering high quality research outputs that are relevant to these goals. In Ethiopia, the main aim of the project is to identify and validate solutions to the problems experienced by small-holder crop–livestock farmers. Africa RISING takes an integrated approach to strengthen farming systems. It conducts participatory research that identifies technologies and management practices that work for farmers and take account of contextual issues like markets for inputs and outputs, community and other institutions and policy environments that influence farm households. AICCRA is a three years (2021-2023) project that operates in six African countries (Ethiopia, Kenya, Zambia, Senegal, Mali and Ghana. The project is supported by a grant from the International Development Association (IDA) of the World Bank and enhances research and capacity-building activities by CGIAR and its partners. AICCRA in Ethiopia aims to strengthen the capacity of targeted national partners and stakeholders of CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa to access and implement at scale validated climate-smart agriculture technologies, climate information services, and climate-informed digital ag-advisories to build the resilience of agri-food systems. The AICCRA project in Ethiopia has eight research activities. Livestock feed and forage options value chain contributes to four of the eight activities, which include capacity building to support implementation of climate-smart agriculture (CSA) technology packages; identification of climate- and gender and social inclusion-smartness of CSA packages; prioritization and awareness increase of best-bet CSA options and approaches for key value chains; and integration of climate-smart options and tailored CSI advisory systems for specific value chains. In line with this, ILRI contracted a consultant to undertake media and communications related activities including media assessment, training of radio journalists on livestock feed and forage innovations and also impact assessment. As part of this, the consultant travelled to three regions of Ethiopia (Amhara, Oromia and SNNPR) and made an assessment to identify appropriate regional radio stations. Following the assessment three media institutions are identified in the three regions and a partnership agreement was signed between ILRI and the media institutions to produce and broadcast radio programs on livestock feed and forage innovations. A two day media training workshop on climate smart feed and forage innovations were organized in Addis Ababa before starting working on the radio program production.